Efikasi diri dan Implementasi Early Warning Scoring System (EWSS) pada Pasien Henti Jantung oleh Perawat Ruang Rawat Inap - Ardiansyah, Diki; Aeni, Linda Nur; Kurnia, Theresia Avila; Jauhar, Muhamad (JURNAL KEPERAWATAN RAFLESIA, 2024)
The incidence of cardiac arrest patients in the world is increasing. Early detection is an important factor in the management of cardiac arrest patients and the parameters used to monitor the patient's condition intensively are called EWSS (Early Warning Scoring System). Success in carrying out these EWSS parameters can be influenced by the role of nurses and nurses' beliefs or self-efficacy. This study analyses the relationship between nurses' self-efficacy in implementing the EWSS in the Cibabat Hospital Inpatient Room. This study used a cross-sectional study with purposive sampling of all nurses in the inpatient room as many as 100 people. The data collection instruments used were self-efficacy questionnaires and observations of completing the EWSS sheet. As many as 51% of respondents have high self-efficacy, and 64% of respondents implement EWSS completely. Based on the chi-square statistical test obtained (? value = 0.001 < = 0.05) it shows that there is a relationship between nurses' self-efficacy in the implementation of EWSS in the Inpatient Room of Cibabat Hospital. There is a relationship between nurses' self-efficacy in implementing EWSS. Researchers recommend the hospital policy to provide training to nurses regarding the implementation of EWSS and update the EWSS parameters into 7 EWSS indicators according to the applicable national theory.